What Does Musicology Have to Do With Archiving? Three Experiences of Engagement - Bertolani, Valentina; Nakai, You; Santacesaria, Luisa (Intersections, 2020)
Musical practices derived from post-1960s experimental music created heterogeneous musical materials and traces—including scores, preparations and instrument modifications, electronic instruments, custom-made devices, and recordings. The Romantic work concept on which most traditional musical archives are based is unsuitable to preserve this expanded apparatus of objects and concepts, and rethinking the musical archive is becoming urgent.This colloquy collected the experiences of three researchers, engaging with five institutions, three creators, and four countries. Yet the archival issues presented are eerily similar. These experiences involve David Tudor (paper-based archive at the Getty Research Institute, Los Angeles, CA, and the David Tudor Instrument Collection at Wesleyan University, Midtown, CT); Mario Bertoncini (paper-based archive at the archive of the Akademie der Künste, Berlin, and his object collection at the moment stored at the Fondazione Isabella Scelsi, Rome); Gayle Young (who still owns all her production).